EVALUASI PENGARUH BAHAYA GEMPA RENCANA TERHADAP POTENSI TIMBULNYA KORBAN JIWA PADA BANGUNAN PEMERINTAH DI KABUPATEN INDRAGIRI HILIR MENGGUNAKAN METODA FEMA P-58-5 - Rofriantona Rofriantona; Ridwan Ridwan; Zulfikar Djauhari (Pelantar Press, 2023)
The FEMA P-58-5 method is a method used to obtain the performance of a building structure using a probability approach. The purpose of this reserach is to obtain the performance of the object prior to pinfluence of the planned earthquake (2017 Earthquake Hazard Map).The object is a government building in Tembilahan City, consists of : Immigration Office, Regent's Office, Puri Husada Hospital and Rusunawa. Geographically, Tembilahan is located at coordinates 103° 9' 28